2014
DOI: 10.3390/ijms15046356
|View full text |Cite
|
Sign up to set email alerts
|

Importance of N-Glycosylation on CD147 for Its Biological Functions

Abstract: Glycosylation of glycoproteins is one of many molecular changes that accompany malignant transformation. Post-translational modifications of proteins are closely associated with the adhesion, invasion, and metastasis of tumor cells. CD147, a tumor-associated antigen that is highly expressed on the cell surface of various tumors, is a potential target for cancer diagnosis and therapy. A significant biochemical property of CD147 is its high level of glycosylation. Studies on the structure and function of CD147 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
103
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 120 publications
3
103
0
Order By: Relevance
“…Three glycosylation sites have been identified within its Ig-like domains and are postulated to serve as a regulatory mechanism of CD147 function (78). Moreover, the nature of oligosaccharides and HG/LG ratio has been shown to affect many diverse physiologic processes central to CD147 from tumor invasion to embryo implantation (79). Our studies show that VH4-34-encoded IgM Abs bound only a particular glycan moiety on CD147; such reagents that distinguish CD147 based on its glycosylation flavor may be useful in unraveling the central role of CD147 in many cellular processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three glycosylation sites have been identified within its Ig-like domains and are postulated to serve as a regulatory mechanism of CD147 function (78). Moreover, the nature of oligosaccharides and HG/LG ratio has been shown to affect many diverse physiologic processes central to CD147 from tumor invasion to embryo implantation (79). Our studies show that VH4-34-encoded IgM Abs bound only a particular glycan moiety on CD147; such reagents that distinguish CD147 based on its glycosylation flavor may be useful in unraveling the central role of CD147 in many cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the CD147-CD98 complex is ubiquitous, SC-PNAL expression on this complex is specific to B lymphocytes, B cell malignancies, and certain epithelial cancers. Expression of SC-PNAL on epithelial cancers varies from high to low and may be a cross-reactive epitope emerging from the aberrant glycosylation linked to malignant transformation (79,80). Nontemplate-based glycosylation is a coordinated, controlled process that leads to many complex glycan products.…”
Section: Discussionmentioning
confidence: 99%
“…3.3. Tumor-associated antigen (CD147) CD147, a tumor-associated antigen, is a transmembrane protein and a member of the immunoglobulin receptor family and is highly expressed on the cell surface of various tumor cells (Bai et al, 2014). The role of CD147 in tumorigenesis is related to the inducement of MMP expression.…”
Section: Adhesion and Signal Moleculesmentioning
confidence: 99%
“…Several mechanisms have been proposed to explain the regulation of CD147 expression, including the following mechanisms: the TGF-β1-CD147 signalling loop in the development of liver fibrosis; the regulatory loop involving miR-22, Sp1, and c-Myc modulating CD147 expression; and the induction of CD147 clustering by galectin-3192021. Among the various mechanisms, the modification of CD147 by N-glycosylation has been demonstrated to be instrumental for the regulation of CD147 function during malignant transformation22. Previous studies have suggested that CD147 deglycosylation by tunicamycin treatment not only results in a failure to induce MMP-1 and MMP-2 expression, but also inhibits the induction of MMPs secretion caused by native CD14723.…”
mentioning
confidence: 99%